2016
DOI: 10.1080/02699931.2016.1244044
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in attention to disgust facial expressions

Abstract: Research demonstrates that women experience disgust more readily and with more intensity than men. The experience of disgust is associated with increased attention to disgust-related stimuli, but no prior study has examined sex differences in attention to disgust facial expressions. We hypothesised that women, compared to men, would demonstrate increased attention to disgust facial expressions. Participants (n = 172) completed an eye tracking task to measure visual attention to emotional facial expressions. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Our framework predicts that the broader suite of affective experiences that motivate and enable costly avoidance of different types of harm should show similar demographic patterns to those we report for disgust. A full review is beyond our present scope, but, as noted above, fear, anxiety, worry, and pain do indeed seem to be more pronounced among women (Else-Quest et al, 2006; Feingold, 1994; Fillingim et al, 2009; Keogh, 2012; McLean & Anderson, 2009; McLean et al, 2011), as do related processes such as attention to others’ disgust (Kraines, Kelberer, & Wells, 2016). Similarly, emotions that motivate risk-taking, such as anger, should show reversed patterns (Fessler et al, 2004; Sell et al, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…Our framework predicts that the broader suite of affective experiences that motivate and enable costly avoidance of different types of harm should show similar demographic patterns to those we report for disgust. A full review is beyond our present scope, but, as noted above, fear, anxiety, worry, and pain do indeed seem to be more pronounced among women (Else-Quest et al, 2006; Feingold, 1994; Fillingim et al, 2009; Keogh, 2012; McLean & Anderson, 2009; McLean et al, 2011), as do related processes such as attention to others’ disgust (Kraines, Kelberer, & Wells, 2016). Similarly, emotions that motivate risk-taking, such as anger, should show reversed patterns (Fessler et al, 2004; Sell et al, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…Firstly, our sample was entirely female, and so it is plausible that the current findings may not be generalisable to males. For instance, sex differences have been observed in self-report ratings of negative affect and fronto-limbic connectivity during emotional processing (Lungu et al 2015) when attending to disgust facial expressions (Kraines et al 2017) and during response inhibition in emotional contexts (Ramos-Loyo et al 2016). Further research is needed to investigate if the observed effects of emotional stimuli reported here in females are also evident for males.…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation for this difference is that the Cisler et al sample included both male and female university students, while van Hooff and colleagues’ sample was restricted to females. Indeed, there are important gender differences in the experience of disgust (Oaten, Stevenson, & Case, 2009) and frequency of attending to disgust cues (Kraines, Kelberer, & Wells, 2016). Differences in stimulus cues may also account for discrepant findings, as Cisler and colleagues used emotion-relevant words, whereas van Hooff and colleagues used emotional images.…”
Section: Cognitive Biases and Disgust: What Have We Learned?mentioning
confidence: 99%
“…For example, women are consistently found to have greater disgust proneness than men (Oaten, Stevenson, & Case, 2009), which may be related to evolutionary pressures (Fessler, Eng, & Navarrete, 2005; Fleischman & Fessler, 2011). Although there is a paucity of research examining gender differences in cognitive bias for disgust, one study did find that women demonstrate a greater attentional bias toward disgust compared to men, based on analysis of viewing patterns of emotional faces (Kraines, Kelberer, & Wells, 2016). However, it remains unclear if gender differences in cognitive bias for disgust account for the gender differences in some anxiety disorder.…”
Section: A Combined Cognitive Bias Hypothesis For Disgustmentioning
confidence: 99%